2008
DOI: 10.1093/hsw/33.1.23
|View full text |Cite
|
Sign up to set email alerts
|

A Retest of Two HIV Disclosure Theories: The Women's Story

Abstract: The purpose of this study was to evaluate the applicability of two theories of HIV disclosure previously tested with men. Participants included 125 HIV-positive women enrolled in a larger, longitudinal study of HIV disclosure and mental health. Structural equation modeling was used to analyze the proposed theoretical models. The disease progression model contained two single-indicator exogenous variables (disease progression) and one endogenous latent variable (disclosure). The original consequences model cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 20 publications
3
51
0
Order By: Relevance
“…The Consequence Theory of HIV disclosure has been studied in women, and posits that an individual will weigh the possible consequences of disclosure before making a decision to disclose their status. 28,29 Some evidence suggests that women may tend to prioritize the needs of others over their own needs when evaluating the consequences of disclosure. 29 Brief interventions based in principles of cognitive behavioral therapy may be helpful in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Consequence Theory of HIV disclosure has been studied in women, and posits that an individual will weigh the possible consequences of disclosure before making a decision to disclose their status. 28,29 Some evidence suggests that women may tend to prioritize the needs of others over their own needs when evaluating the consequences of disclosure. 29 Brief interventions based in principles of cognitive behavioral therapy may be helpful in this context.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Some evidence suggests that women may tend to prioritize the needs of others over their own needs when evaluating the consequences of disclosure. 29 Brief interventions based in principles of cognitive behavioral therapy may be helpful in this context. Specifically, providers can help women identify fears around disclosure, identify the pros and cons of disclosure, and teach effective communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviewers highlighted the need for improved measurement (e.g. Obermeyer et al, 2011;Smith et al, 2008), and several authors proposed models to guide research on disclosure (Bairan et al, 2007;Bird & Voisin, 2011;Chaudoir & Fisher, 2010;Chaudoir et al, 2011;Mayfield Arnold et al, 2008;Serovich et al, 2008) and stigma (Bos et al, 2013;Earnshaw & Chaudoir, 2009;Mahajan et al, 2008). However, although most research has focused on the broader process of increasing one's disclosure levels from none or few confidants to the entire social network, the existing theoretical models interpreted all empirical evidence in terms of causes and consequences of single disclosure events.…”
Section: Introductionmentioning
confidence: 99%
“…22 Alternatively, consequence theory proposes that the decision to disclose one's HIV serostatus occurs after a conscientious analysis of the anticipated positive and negative outcomes of that decision. 23 Empirical studies of consequence theory have shown to predict disclosure to friends and family members, but not to sexual partners. 22,26 Finally, the disclosure processes model improves upon previous theories by recognizing the role played by the antecedent goals of disclosure, the mediating processes of disclosure decisions, and the outcomes of these decisions.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] We know there are differences in sexual risk behavior patterns between HIV-infected MSM, men who have sex with women (MSW), and women who have sex with men (WSM). [28][29][30][31][32][33] These differences suggest that the costs, benefits, and outcomes associated with serostatus disclosure may also differ between groups.…”
Section: Introductionmentioning
confidence: 99%